Strategies of Islamic Banks in Reducing Non-Performing Financing (NPF): A Case Study at BPRS Bangka Belitung Branch - Nur Hidayati (Universitas KH. Abdul Chalim Mojokerto, 2025)
Problematic financing or Non-Performing Financing (NPF) is one of the main challenges faced by Islamic banking in maintaining financial stability and soundness. A high level of NPF can negatively affect profitability, liquidity, and customer trust in the bank. This study aims to analyze the strategies implemented by Islamic banks in reducing problematic financing. The research method used is descriptive qualitative with a case study approach at Bank Pembiayaan Rakyat Syariah (BPRS) Bangka Belitung. The results of the study indicate that the average Non-Performing Financing (NPF) ratio remains higher than the standard set by the Financial Services Authority (OJK), which is 5%, and the internal standard of BPRS Bangka Belitung, which is 7%. The strategies carried out by BPRS Bangka Belitung include direct collection, write-off for fully provisioned (100%) PPAP accounts, restructuring, collection through third parties, and simplified lawsuits through the religious court. These strategies have become key measures in reducing the NPF rate. To further optimize the results, it is necessary to strengthen preventive actions at the financing analysis stage through the 5C analysis (Character, Capacity, Capital, Collateral, and Condition) or more comprehensively with 7P analysis (Personality, Purpose, Prospect, Payment, Party, Profitability, and Protection). Strengthening these analytical processes can minimize the occurrence of problematic financing and enhance sustainable performance improvement.